2013
DOI: 10.1002/mame.201300127
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene and Carbon Materials as Components of Styrene-Butadiene Rubber Nanocomposites Prepared by Aqueous Dispersion Blending

Abstract: Emulsifier-free aqueous dispersions of functionalized graphene (FG) represent key intermediates for the production of rubber composites, enabling uniform dispersion of predominantly single FG sheets. In this comparative study on styrene-butadiene rubber (SBR) composites with conventional and novel carbon-based fillers the influence of filler type, content, and dispersion process is examined. For SBR/FG nanocomposites two aqueous dispersion blend strategies based on thermally and chemically reduced graphite oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 37 publications
(58 reference statements)
1
58
0
1
Order By: Relevance
“…These studies, along with the significant work of Kim et al [124] which was discussed Mülhaupt and coworkers investigated the reinforcement of styrene-butadiene rubber (SBR) with reduced GO [201] and functionalized graphene [159]. They obtained significant increases in stiffness and strength upon the addition of both chemically-reduced GO (CRGO) and thermally-reduced GO (TRGO) to SBR and their data are summarised in Table 2.…”
Section: Tensile Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…These studies, along with the significant work of Kim et al [124] which was discussed Mülhaupt and coworkers investigated the reinforcement of styrene-butadiene rubber (SBR) with reduced GO [201] and functionalized graphene [159]. They obtained significant increases in stiffness and strength upon the addition of both chemically-reduced GO (CRGO) and thermally-reduced GO (TRGO) to SBR and their data are summarised in Table 2.…”
Section: Tensile Propertiesmentioning
confidence: 90%
“…There are a number of reports in the literature upon investigations into the mechanical properties of graphene-based/elastomer nanocomposites [112, 124- 185,187,194,195,[200][201][202][203][204]. In most cases some type of reduced graphene oxide was employed as the filler rather than graphene itself.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…With this aim, graphene or GO platelets are often dispersed in the polymer matrix to enhance its barrier properties: the presence of 2D nanosheets in the polymer bulk can significantly reduce the material permeability, as demonstrated in several different works [10,11]. The intrinsic barrier ability of graphene towards gases and vapors, together with its remarkable aspect ratio, has allowed the fabrication of composites with improved performances [12][13][14][15][16]. Among others, Compton et al reported a significant improvement of the barrier properties by M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT incorporating 2.27 % vol.…”
Section: Introductionmentioning
confidence: 98%
“…[12,13] The extraordinary properties of graphene and its ability to disperse in polymeric matrices have created a new class of polymer nanocomposites. [14][15][16] Graphene is the two-dimensional (2-D) allotrope of carbon, composed only of sp2 carbon atoms arranged in a honeycomb structure. [17,18] In this study, multilayer graphene (MLG) is proposed as a promising new nanofiller.…”
Section: Introductionmentioning
confidence: 99%